2018
DOI: 10.1051/0004-6361/201629017
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of an electron beam through the solar corona with LOFAR

Abstract: The Sun's activity leads to bursts of radio emission, among other phenomena. An example is type-III radio bursts. They occur frequently and appear as short-lived structures rapidly drifting from high to low frequencies in dynamic radio spectra. They are usually interpreted as signatures of beams of energetic electrons propagating along coronal magnetic field lines. Here we present novel interferometric LOFAR (LOw Frequency ARray) observations of three solar type-III radio bursts and their reverse bursts with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…An increase in the inferred beam velocity from type III bursts has recently been reported by Mann et al (2018) using LOFAR imaging observations below 100 MHz. Mann et al (2018) derive velocities from the onset time of the type III burst at different frequencies and found huge increases in derived beam velocities around 30 MHz, with some bursts reported as superluminal.…”
Section: Beam Velocity Evolutionmentioning
confidence: 60%
See 2 more Smart Citations
“…An increase in the inferred beam velocity from type III bursts has recently been reported by Mann et al (2018) using LOFAR imaging observations below 100 MHz. Mann et al (2018) derive velocities from the onset time of the type III burst at different frequencies and found huge increases in derived beam velocities around 30 MHz, with some bursts reported as superluminal.…”
Section: Beam Velocity Evolutionmentioning
confidence: 60%
“…An increase in the inferred beam velocity from type III bursts has recently been reported by Mann et al (2018) using LOFAR imaging observations below 100 MHz. Mann et al (2018) derive velocities from the onset time of the type III burst at different frequencies and found huge increases in derived beam velocities around 30 MHz, with some bursts reported as superluminal. Whilst the effect we describe above can increase the derived beam velocity from radio bursts, and could play a role in the findings of Mann et al (2018), it is not likely to explain three-fold increases in velocities, nor provide superluminal velocities.…”
Section: Beam Velocity Evolutionmentioning
confidence: 60%
See 1 more Smart Citation
“…Radio imaging of these bursts at a wide range of densely sampled frequencies with a sufficiently high temporal cadence can be used to map the detailed trajectory of a propagating electron beams in the corona, providing an excellent means of tracing these beams to their acceleration sites. Previous radio imaging of type III bursts (and their variants such as type J and U bursts) at one or several discrete frequencies, particularly from solar-dedicated Culgoora, Clark Lake, and Nançay radioheliographs, as well as general-purpose radio interferometers such as the Very Large Array, has yielded important results on the location and propagation of electron beams in the corona (e.g., Dulk & Suzuki 1980;Gopalswamy et al 1987;Aschwanden et al 1992;Paesold et al 2001;Klein et al 2008;Saint-Hilaire et al 2013;Carley et al 2016 (Morosan et al 2014;Kontar et al 2017;Reid & Kontar 2017;McCauley et al 2017;Mann et al 2018;Cairns et al 2018). However, in order to trace the electron beams to the immediate vicinity of the primary magnetic energy release and electron acceleration site, presumably located in the low corona where the plasma is denser (typically at the order of 10 10 cm −3 ; Aschwanden 2002; Krucker et al 2008), spectral imaging of type III bursts at shorter, decimetric wavelengths ("dm-λ" hereafter) is preferred because ν pe , which increases monotonically with n e , falls into this wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…The trapped radio waves only leave the flux tube at the apparent source position when the wave frequency inside the tube is greater than the plasma frequency outside. Such displacements of the apparent radio source have also been seen in radio images from the LOw Frequency ARray (LOFAR; Kontar et al 2017;Mann et al 2018) at metric wavelengths. Based on a study of fine structures of Type III radio bursts using LOFAR observations, Kontar et al (2017) suggested that the apparent source locations of fundamental and harmonic emission result from the scattering of radio waves by coronal density inhomogeneities.…”
Section: Introductionmentioning
confidence: 73%